Profit: A new key concept in Russia and the Czech Republic. Parallels and differences - Johanna Petters; Barbara Müller (Journal for East European Management Studies, 2004)
The article describes how the concepts - i.e. people's knowledge and attitude - connected to the Russian and Czech words for profit have changed during the transformation after 1989. In the socialist period capitalist profit maximization is stereotypically damned whereas socialist profit remains rather an internal matter of the enterprises. In the 1990ies both the profits of particular enterprises and the general notion of profit become a public matter. In specialized and newspaper texts profit is endorsed as a motivation for people to work and the driving economic force. In Czech spoken discourse people are often skeptical towards the notion of profit. – – Der Artikel beschreibt, wie sich nach der Wende von 1989 die Konzepte - d.h. Wissen und Einstellungen - zum russischen bzw. tschechischen Wort für Gewinn verändert haben. In den Texten aus sozialistischer Zeit wird kapitalistischer Gewinn stereotyp verurteilt. Sozialistischer Gewinn ist meistens eine interne Angelegenheit der Betriebe und nur eine von mehreren Kennziffern. In den 1990ern wird Gewinn zu einer Sache, die alle angeht: Er wird als wichtigstes Betriebsergebnis veröffentlicht; der Begriff wird eingehend diskutiert. In Fachund Zeitungstexten wird er als Arbeitsmotivation und treibende wirtschaftliche Kraft positiv bewertet. Im tschechischen Alltagsdiskurs herrscht eine skeptische Einstellung gegenüber Gewinn bzw. Gewinnstreben vor.
Keywords: 650; Profit; Economic transformation; Corpus linguistics; Key words concept